Can a Ban on Child Labour Be Self-Enforcing, and Would It Be Efficient? - Alessandro Cigno (Center for Economic Studies and ifo Institute (CESifo), 2024)
Basu and Van (1998) show that a ban on child labour may be self-enforcing under the extreme assumption that, above the subsistence level, no amount of consumption can compensate parents for the disutility of child labour. We show that a partial ban may be self-enforcing also in a more general model where education is an alternative to work, and the disutility of child labour can be compensated by higher present consumption or future income, but a total ban may not. We also show that, in the absence of informational asymmetries, child labour can be eliminated and a First Best achieved if the ban is combined with a credit-backed policy including a subsidy to parents, and a tax on skilled adults. A First Best is out of reach of the use children make of their time when they are neither at school, nor working in the labour market is private information, because the policy maker then faces an incentive-compatibility constraint. The Second-Best policy reduces child labour, but not to zero.
Keywords: H31; J22; O12; 330; child labour; education; fertility; credit; taxes; subsidies; uncertainty; asymmetric information